Angueira, Anxo (2022): "Palmeiras, piueiros". Santiago de Compostela: Chan de Pólvora (Col. Cova da Lontra, nº 6), 179 pp. - Cruz Pérez, María Sonia (Madrygal. Revista de Estudios Gallegos, 2023)
Review of the book Palmeiras, piueiros by Anxo Angueira (Santiago de Compostela: Chan de Pólvora, Cova da Lontra series, no. 6, 2022), by María Sonia Cruz Pérez.